Mechanical wear and oxidative degradation analysis of retrieved ultra high molecular weight polyethylene acetabular cups - Choudhury, Dipankar; Ranuša, Matúš; Fleming, Robert A.; Vrbka, Martin; Křupka, Ivan; Teeter, Matthew G.; Goss, Josh; Zou, Min (Journal of the mechanical behavior of biomedical materials, 2018)
The number of revision joint replacements has been increasing substantially over the last few years. Understanding their failure mechanism is extremely important for improving the design and material selection of current implants. This study includes ten retrieved and four new mildly cross-linked ultra-high molecular weight polyethylene (UHMWPE) acetabular liners. Among them, most of the prostheses (n = 5) were reported to be revised and replaced due to aseptic loosening, followed by painful joint (n = 2), dislocation (n = 1), intra articular ossification (n = 1), combination of wear (liner) and osteolysis (stem) (n=1). Surface deviations (wear, material inflation and roughness), oxidative degradation and change of material properties were measured using micro-computed tomography (micro-CT) scan, 3D laser scanning microscopy, raman spectroscopy and nanoindentation, respectively. Prostheses having eccentric worn areas had much higher linear wear rates (228.01 ± 35.51µm/year) compared to that of centrically worn prostheses (96.71 ± 10.83µm/year). Oxidation index (OI) showed similar trends to the surface penetration depth. Among them, sample 10 exhibited the highest OI across the contact area and the rim of the cup liner. It also had the lowest hardness/elasticity ratio. Overall, wear and creep, oxidative degradation and reduced hardness/elasticity ratio all contributed to the premature failure of the UHMWPE acetabular cup liners.